Rancang Bangun Sistem Pengiriman Paket Penerobos Kemacetan Berbasis Teknologi Drone - Handy M Irawan; Agus Sofwan (Institut Sains dan Teknologi Nasional, 2023)
Abstract Package delivery systems in Indonesia, especially in big cities, are currently less efficient in terms of delivery speed and are not environmentally friendly, besides that traffic congestion conditions are the most significant thing, therefore in this study a drone was made as a package delivery tool by air as breakthrough of traffic jam that can lift a package or document with a 1000 gram weight that will get to the destination faster than using package delivery using motorized vehicles by land. This research uses a developmental research method to design a drone that is in accordance with certain specifications, then the following stages are carried out: collecting data and information, determining frame design, determining hardware specifications, assembling all hardware, wiring electrical equipment, setting up mission planner software, flight tests without loads, flight tests with certain loads, collecting test data. As for the control communication system, it uses a telemetry that is connected in real time between the ground system equipment and the equipment in the air or air system. From the test results obtained drones that can work well. This is evidenced by looking at the experimental data for flight endurance testing, flight speed testing to flight testing with certain loads of flight testing data with a certain range, Keywords: Drone technology, Telemetry, traffic jam, Delevery system